"Now is the time for all good men --" - Fischetti, John R. (1953)
Cartoon shows a seesaw weighed down on one end by a huge bag of money labeled "Unbalanced Budget." At the other end, the GOP elephant exhorts people from a group advocating a "Tax Cut First" to climb aboard and balance the budget first. Reflects the reluctant conclusion of the Eisenhower Administration that a balanced budget took priority over the reduction of taxes promised during the 1952 election campaign.
Keywords: Government spending policy; Taxes; Seesaws